Guided bone regeneration with or without a collagen membrane in rats with induced diabetes mellitus: Histomorphometric and immunolocalization analysis of angiogenesis and bone turnover markers - Jardini, Maria Aparecida Neves [UNESP]; Tera, Tï¿½bata de Mello [UNESP]; Meyer, Augusto Cesar de Andrade [UNESP]; Moretto, Camilla Magnoni [UNESP]; do Prado, Renata Falchete [UNESP]; Santamaria, Mauro Pedrine [UNESP] (Quintessence Publishing, 2016)
Purpose: Diabetes mellitus (DM) affects the processes of repair, wound healing, and bone remodeling. This study was conducted to evaluate autologous bone graft integration, either with or without guided bone regeneration, through analyzing the expression of bone reabsorption markers and neovascularization in rats suffering from DM. Materials and Methods: Thirty adult Wistar rats were divided into two groups: The DM group received an injection of alloxan monohydrate (150 mg/kg), and the control group received an injection of sterile saline. Fifteen days afterward, an autologous bone grafting was performed in each of their arches, with the insertion of a membrane into the left arch. Euthanasia occurred in 7, 21, or 60 days after the surgery. Bone samples were processed for histomorphometric and immunohistochemical analyses. Results: After a statistical analysis of the data, the presence of DM did not interfere negatively in the bone autograft repair. The collagen membrane favored the graft integration into the recipient bed and the bone neoformation around the graft. Greater vascularization was observed between 21 and 60 days after the surgery, which increased bone formation and resulted in the graft integration. Only the RANK marker showed a significant difference in the glycemic groups. Transglutaminase 2 was significant for the membrane presence and experimental time. Conclusion: It is hence concluded that diabetes mellitus does not interfere with bone reabsorption via the RANK/RANKL/OPG. The graft integration was similar between the groups; however, the results of hyperglycemia with the collagen membrane indicate greater bone growth after graft placement.
Keywords: Angiogenesis; Bone reabsorption; Diabetes mellitus; Guided bone regeneration; RANK/RANKL/ OPG; Transglutaminase 2; VEGF